Accession-Dependent CBF Gene Deletion by CRISPR/Cas System in Arabidopsis - Cho, Sungkyung; Yu, Si-in; Park, Junghoon; Mao, Yanfei; Zhu, Jian-Kang; Yun, Dae-Jin; Lee, Byeong-ha (Frontiers in Plant Science, 2017)
The CRISPR/Cas system became a powerful genome editing tool for basic plant research and crop improvement. Thus far, CRISPR/Cas has been applied to many plants, including Arabidopsis, rice and other crop plants. It has been reported that CRISPR/Cas efficiency is generally high in many plants. In this study, we compared the genome editing efficiency of CRISPR/Cas in three different Araibidposis accessions [Col-0, Ler, and C24RDLUC (C24 accession harboring the stress-responsive RD29A promoter-driven luciferase reporter)]. For the comparison, we chose to target the cold-responsive C-repeat/DRE-Binding Factor (CBF) genes. CBF1, CBF2, and CBF3 genes are tandemly located on Arabidopsis chromosome 4 with redundant functions as the key transcription factors functioning in cold stress signaling and tolerance. Due to the close proximity of these CBFs on the chromosome, it is impossible to generate cbf1, cbf2, cbf3 triple mutants (cbf123) by traditional genetic crosses. Therefore, using the CRISPR/Cas tool, we aimed to generate cbf123 mutants and compared the genome editing efficiency in different Arabidopsis accessions. Among the accessions, Ler was the most resilient to the CRISPR/Cas deletion with the lowest gene deletion ratio in both T1 and T2 generations. Interestingly, while C24RDLUC showed a high CBF123 deletion frequency in T2 only when the gene deletion was observed in T1 generation, Col-0 displayed high ratios of the CBF123 deletions in T2 regardless of the presence or absence of the CBF123 deletion in T1. Isolated cbf123 mutants in C24RDLUC background showed no expression of CBF1, CBF2, and CBF3 genes and proteins with reduction in the CBF target gene expression under cold stress.